Karakteristik Gel Lidah Buaya sebagai Edible Coating Ditinjau dari Suhu dan Lama Penyimpanan - Felipus Muni; Luh Suriati; Anak Agung Made Semariyani (GEMA AGRO, 2019)
The use of edible coatings has long been known as an alternative to extend the shelf life of fruits. One natural ingredient that can be used as an edible coating is aloe vera gel which is rich in functional components. Aloe vera gel enzyme activity is very high. To maintain its stability it must be stored at the right temperature. The purpose of this study was to determine the stability of aloe vera gel as an edible coating in terms of temperature treatment and storage time. This research was conducted for 5 months from March-July 2019 in the Food Analysis Laboratory of the Faculty of Agriculture, Warmadewa University. This research is a factorial experiment with a Completely Randomized Design (CRD) consisting of 2 (two) factors, namely: factor I, storage temperature (S) consisting of 2 levels namely room temperature (S1) and cold temperature (S2). Factor II, storage time consists of 8 levels, namely 1 day, 2 days, 3 days, 4 days, 5 days, 6 days, 7 days and 8 days. Variables observed for stabilization of aloe vera gel as an edible coating include observations of physical analysis (weight and color), analysis of chemical properties (degree of acidity (pH), moisture content, and viscosity), biological analysis (microbial total test). The best stability of edible aloe vera gel coating is obtained from the cold temperature treatment with a storage time of 4 days